Allelopathic potential of Plectranthus barbatus Andrews on Lactuca sativa L. and Bidens pilosa L. seeds germination - Azambuja, Natasha; Hoffmann, Clairomar Emilio Flores; Neves, Luiz Augusto Salles das (Revista de Ciências Agroveterinárias, 2010)
Aqueous extracts from dry leaves of Plectranthus barbatus Andrews (EBIN), in concentrations of 0; 25, 50, 75, and 100% (v/v), were prepared with the objective of studying the allelopathic potential of this medicinal species on Lactuca sativa L. and Bidens pilosa L. seeds. The experiment was carried out in January of 2009, at the Genetic Laboratory of Santa Maria Federal University. The first count germination (PCG), germination (G), germination speed index (IVG) and shoot and root length were evaluated. All parameters were affected by EBIN of P. barbatus from the lower concentration on. The seeds and seedlings of B. pilosa presented greater sensitivity to the extracts than those of L. sativa. The results allow us to infer that EBIN of P. barbatus have allelopathic potential.